Enhancing Women’s Role in the Rehabilitation of Degraded Common Lands: Experiences in the Aravalli Project, Haryana - Rawat, J. K.; Bedi, H. (Indian Forester, 1997)
The Aravalli Project in Haryana aims at rehabilitating common lands of the hilly villages in the southern part of the State. Women being the primary collectors of fodder, firewood and other produce from the common lands, have a greater stake in its rehabilitation and a major role in its conservation and management. This paper describes why and how to obtain involvement of the rural women in these activities. It also presents the approaches adopted, the challenges faced and progress made in implementation of Women-in-Development programme by the Project.